ANALYSIS OF FACTORS RELATED TO THE COMPLETENESS OF PRIMARY IMMUNIZATION IN CHILDREN IN DESA UJUNG BAWANG SINGKIL - Safitri, Faradilla (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
Immunization is an attempt to confer immunity in children with a vaccine insert into the body so that the body makes antibodies to prevent certain diseases. Data from the Health Department of Aceh Singkil, immunization coverage in 2015 amounted to 87.5%, but in Puskesmas Singkil are villages that immunization coverage does not meet the standards of the Universal Coverage Imunization (UCI) is the village of Ujung Onions (69.0%). To analyze the factors related to the completeness of basic immunization in infants in the village of Ujung Onion Singkil Year 2017. Type of analytical research with cross-sectional approach. Results: Univariate analysis showed 69.0% children get complete immunization, 69.0% of mothers with low education, 71.4% of mothers of high knowledge, 90.5% of mothers did not work, 69.0% of mothers with many children <3, 57.1% of women are positive and 54.8% within health services are close by. The results of the bivariate analysis obtained education (p-value = 1.000), knowledge (p-value = 0.000), employment status (p-value = 1.000), the number of children (p-value = 0173), attitude (p-value = 0.008) and affordability of health care settings (p-value = 0354). No correlation between knowledge and attitude to complete basic immunization in infants whereas there is no relation between education, employment status, number of children and affordability of health services with complete basic immunization in infants in the village of Ujung Bawang Singkil Year 2017. It is expected that the health professionals can Singkil make counseling accompanied by the distribution of brochures and banners on the importance of provision of basic immunization in children.Keywords: Basic immunization, knowledge, attitudes